2020
DOI: 10.2196/17558
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Activity and Diet Program Delivered by Artificially Intelligent Virtual Health Coach: Proof-of-Concept Study

Abstract: Background Poor diet and physical inactivity are leading modifiable causes of death and disease. Advances in artificial intelligence technology present tantalizing opportunities for creating virtual health coaches capable of providing personalized support at scale. Objective This proof of concept study aimed to test the feasibility (rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
206
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(211 citation statements)
references
References 34 publications
3
206
2
Order By: Relevance
“…Patients actively engaged with the chatbot, reported experiencing positive progress toward their goals, and deemed the chatbot helpful. One proof-of-concept study [ 45 ] reported on the Paola chatbot, which provided educational messages on physical activity and diet, weekly check-ins, and answers to user questions. The results showed that participants reported relevant weight loss and improved diet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients actively engaged with the chatbot, reported experiencing positive progress toward their goals, and deemed the chatbot helpful. One proof-of-concept study [ 45 ] reported on the Paola chatbot, which provided educational messages on physical activity and diet, weekly check-ins, and answers to user questions. The results showed that participants reported relevant weight loss and improved diet.…”
Section: Methodsmentioning
confidence: 99%
“…The above-reviewed chatbots showed preliminary evidence supporting the efficacy of using chatbots to deliver physical activity and diet interventions. It is worth noting that four out of seven (57.1%) studies reported chatbots as the only intervention used to deliver behavior change strategies [ 26 , 43 , 44 , 46 ], whereas the other three articles reported chatbots as an auxiliary component complementing other intervention approaches such as messages and conversations delivered by human facilitators [ 41 , 42 , 45 ] ( Multimedia Appendix 1 ). The reviewed chatbots were designed with different theoretical components and varied in their abilities to engage in natural language conversations, relationship building, and emotional understanding.…”
Section: Methodsmentioning
confidence: 99%
“…The current study was a secondary analysis process evaluation of a 12-week lifestyle physical activity and healthy eating (based upon the Mediterranean dietary pattern) program delivered via a virtual health assistant in a single-arm repeated measures study. Full details of the virtual health assistant, study methods, and primary outcomes have been published elsewhere [19]. Briefly, over the 12-week study period, participants significantly increased their self-reported weekly moderate-to-vigorous physical activity (MVPA) by 110 min, increased their diet quality scores by 150%, lost 1.3 kg in body weight, and lost 2.1 cm from their waist circumference (all p < 0.05) [19].…”
Section: Methodsmentioning
confidence: 99%
“…Full details of the virtual health assistant, study methods, and primary outcomes have been published elsewhere [19]. Briefly, over the 12-week study period, participants significantly increased their self-reported weekly moderate-to-vigorous physical activity (MVPA) by 110 min, increased their diet quality scores by 150%, lost 1.3 kg in body weight, and lost 2.1 cm from their waist circumference (all p < 0.05) [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation